Empirical Research of Mandarin Popularization Boosting County-level Innovation and Entrepreneurship in Ethnic Minority Regions: Evidences from Eight Counties (Cities) in Guangxi Sino-Vietnam Border (JOURNAL OF ADVANCES IN LINGUISTICS, 2020)
From the perspective of the transaction cost theory, this paper analyzes that the mandarin popularization in ethnic minority regions helps reduce the transaction cost, enhances trust, results in the "innovation and entrepreneurship" effect, and improves the action mechanism of the county-level innovation and entrepreneurship rate. Furthermore, based on the complete sample investigation results of rural residents within 0-3km in eight counties of Sino-Vietnam border, it constructs the quantitative model to conduct the empirical analysis of the significant positive role played by mandarin popularization in the county-level innovation and entrepreneurship in ethnic minority regions, which is that when the mandarin level is changed by 1%, the county-level innovation and entrepreneurship rate is changed by 0.397%.